(3QSGdI aj hGLHGJ GdUdGIs - (3GdcQcj, GdYGedj, CHh GdMSf, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj, J (B940(3g`s
(3ChdgG (B:s
(3hESYGag HbVGA MGLJg ef CbQH GdbQHGJ Cf CcJH QSGdI ehLRI JTJed Ydi hGLHGJ GdUdGIs
(3BNQgG (B:s
(3hcd GdfhGad QcYJGf HJTgO hJSdje EdG GdhJQ aEfgG QcYI (B...s
(3JHUQI GdeDda (B:s
(3GdTgjQ HGdeMbb GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B4(3,U(B281s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B430s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B744s
Keywords: (3abg GdePGgH GdCNQis